SISTEM INFORMASI BURSA KERJA KHUSUS (BKK) : Studi Kasus: SMK Padakembang - Indra Maulana Yusup Kusuma; Linda Apriyanti; Dede Ali Mukti (LPPM STMIK BANDUNG, 2019)
Special Job Exchanges (BKK) in Vocational High Schools are useful for disseminating job vacancy information to students / alumni. This system is useful to disseminate job vacancy information from companies that work with these schools, with the existence of the SPECIAL WORK EXCHANGE SYSTEM INFORMATION PADAKEMBANG VOCATIONAL SCHOOL will facilitate schools to channel their alumni to the real world of work in this BKK information system there is a detailed and digital report later it will help simplify the work of the BKK manager. On the company side it will also be easier to get the desired candidate. In addition to facilitating the time needed it will also be faster so that it can cut down unemployment rates after graduation. The method used is Research and Development (R & D) which refers to the R & D method of Sugiyono. There are 10 steps in this study namely: Potential problems, Data collection, Product design, Design validation, Design revision, Product testing, Product revision, Usage testing, Product revision, Mass production.The results of this study are to overcome the distribution of vacancy information that has not been centralized, and produce a detailed report on applicants' data by developing a special job market information system at Padakembang Vocational School.